Individualized antibiotic strategies. Issue 2 (April 2016) - Taccone, Fabio S.; Bond, Ottavia; Cavicchi, Federica Z.; Hites, Maya
Abstract : Purpose of review: Infections are common complications in critically ill patients and are frequently treated with antibiotics. Unfortunately, delivery of optimal therapy is complicated because efficacy of antimicrobials is influenced by the timing of treatment initiation, the use of combination therapy, and the optimization of drug dosing. Recent findings: Early diagnosis of infection is mandatory to provide a rapid and appropriate antibiotic therapy. The presence of less susceptible strains, in particular for hospital-acquired infections, or patients with severe disease, such as the presence of septic shock, may need combination antibiotic therapy. Antibiotic pharmacokinetics, notably volume of distribution and total body clearance, are significantly altered in these critically ill patients and can influence the attainment of adequate circulating levels when standard dosage regimens are administered. Higher dosing should be considered in such patients, although in case of renal impairment and reduced clearance, drug accumulation could also result in some side-effects. Nebulized antibiotics may provide a better clinical response than systemic antibiotics in ventilator-associated pneumonia because of multidrug-resistant pathogens. Summary: The optimal use of antibiotics in the management of severe infections is an important challenge for ICU physicians. Antimicrobial therapy needs to be individualized according to specific patient characteristics, infecting organisms, and susceptibility patterns.